Chapter On the dynamism of aspectual pair formation in Czech - Esvan, François (Biblioteca di Studi Slavistici, 2017)
This paper aims to analyze the relationship between. perfectivisation and secondary imperfectivisation in Czech. Recent data show for loan verbs a strong tendency, after a short phase of biaspectualism, towards the creation of aspectual pairs through perfectivisation, e.g. bukovat - zabukovat (to book). This step does not necessarily conclude the process, since secondary imperfectives like zabukovávat are also frequent. This development is in opposition to the tendency towards the elimination of secondary imperfectives, which characterized the historical evolution of the Czech language (Šlosar 1981).